Twentieth century women of courage - Escott, Beryl E. (Stroud : Sutton, 1999)
Courage is not unique to one nation or age group, nor is it limited to the Armed Forces, but is evident in all walks of life. While much has been written about the bravery of men, many of the stories behind the awards for bravery to women have been overlooked and their records are sparse. This text provides the names and deeds of women who have distinguished themselves through courage from the beginning of the 20th century to the present day. Squadron Leader Beryl Escott describes hundreds of acts of the most outstanding bravery in the face of almost overwhelming danger, where women have placed their own lives at risk, usually to save lives and sometimes dying in the attempt. Among the many awards mentioned and illustrated are the George Cross, Medal of Honor, Cross of Valour, Star of Courage, Woltemade Decoration and the Florence Nightingale Medal, together with medals from societies great and small, such as the Royal Humane Society, Lloyd's and the Carnegie Hero Fund Trust. Other names appear too, who deserved but received little or no recognition.
The military medal -- The medal of the order of the British Empire 1917-22 -- The Albert, Edward and Empire Gallantry medals -- The George Cross and George Medal -- Women in the armed services -- Service nurses -- The women of SOE in France -- Civilian nurses -- Women of the police, fire and prison services -- Civilian gallantry MBEs. BEMs and commendations for bravery -- Two civiliam societies -Loyd's and the Royal Humane Society -- Other civilian societies' awards and some forgotten women -- American women of the first world war -- American servicewomen of the second world war and beyond -- America -- mainly civilian awards -- Women of America's OSS -- Canadian services and police -- The Canadian horours system -- Some Canadian societies -- Australian women of two world wars -- Australia's own bravery awards -- Other Australian awards -- New Zealand civilian and service awards -- New Zealand awards from other societies -- South African awards.
Includes bibliographical references (pages-273266) and indexes.
Keywords: Women heroes -- Biography; Women -- History; Women; Women heroes